Molecular Evolution of the Yersinia Major Outer Membrane Protein C (OmpC). (January 2016) - Stenkova, Anna M.; Bystritskaya, Evgeniya P.; Guzev, Konstantin V.; Rakin, Alexander V.; Isaeva, Marina P.
The genus Yersinia includes species with a wide range of eukaryotic hosts (from fish, insects, and plants to mammals and humans). One of the major outer membrane proteins, the porin OmpC, is preferentially expressed in the host gut, where osmotic pressure, temperature, and the concentrations of nutrients and toxic products are relatively high. We consider here the molecular evolution and phylogeny of Yersinia ompC. The maximum likelihood gene tree reflects the macroevolution processes occurring within the genus Yersinia. Positive selection and horizontal gene transfer are the key factors of ompC diversification, and intraspecies recombination was revealed in two Yersinia species. The impact of recombination on ompC evolution was different from that of another major porin gene, ompF, possibly due to the emergence of additional functions and conservation of the basic transport function. The predicted antigenic determinants of OmpC were located in rapidly evolving regions, which may indicate the evolutionary mechanisms of Yersinia adaptation to the host immune system.